Association of Bariatric Surgery and Risk of Cancer in Patients With Morbid Obesity. Issue 1 (January 2022) - Khalid, Syed I.; Maasarani, Samantha; Wiegmann, Julia; Wiegmann, Aaron L.; Becerra, Adan Z.; Omotosho, Philip; Torquati, Alfonso
Abstract : Objective: This study investigates the rates of obesity-related cancers in patients undergoing vertical sleeve gastrectomy (VSG), Roux-en-Y gastric bypass (RYGB), or no surgical intervention. Summary Background Data: Obesity has been previously associated with increased rates of cancers; however, weight loss surgeries have not been explored to demonstrate their potential risk reduction impact. Methods: Patients meeting bariatric eligibility criteria between January 2010 and December 2018 were identified. Exact 1:1:1 matching based on baseline patient demographics and comorbidities was used to create 3 groups with identical covariates: patients undergoing VSG, RYGB, and no surgery. Results: A total of 28, bariatric-eligible patients equally split into patients undergoing VSG (n = 9636, 33.3%), RYGB (n = 9636, 33.3%), and those with no surgical intervention (n = 9636, 33.3%). Bariatric-eligible patients that did not undergo surgical intervention had significantly higher rates and odds of developing numerous cancer types included in our study when compared to either surgical cohorts, with any cancer type (4.61%), uterine (0.86%), colorectal (0.57%), and lung cancers (0.50%) being most common. Individuals undergoing RYGB were significantly less likely to develop colorectal cancer compared to patients without any surgical intervention [odds ratio (OR) 0.47, 95% confidence interval (CI) 0.30–0.75]. Additionally, those undergoing VSG were significantly less likely to develop lung cancer than the bariatric eligible no surgery cohort (OR 0.42, 95% CI 0.25–0.70). Conclusion: Postoperative rates of any cancer type, lung, ovarian, and uterine cancer were significantly lower in obese patients undergoing either vertical sleeve gastrectomy (VSG) or RYGB compared to bariatric-eligible patients without any surgical intervention. Abstract : Supplemental Digital Content is available in the text